A phylogenetic analysis of Biycon and Henochilus (Characiformes, Characidae, Bryconinae) based on the mitochondrial gene 16S rRNA - Silva Hilsdorf, Alexandre Wagner; Oliveira, Claudio [UNESP]; Thadeo de Lima, Flavio Cesar; Matsumoto, Cristianne Kayoko (Soc Brasil Genetica, 2008)
The genus Btycon, the largest subunit of the Bryconinae, has 42 valid species distributed from southern Mexico to the La Plata River in Argentina. Henochilus is a monotypic genus, comprising a single species (H. wheatlandil) found in the upper Rio Doce basin. In the present study, partial sequences of the mitochondrial gene 16S were obtained for fifteen species of Brycon and for Henochilus wheatlandii. The results showed that the genus Brycon is paraphyletic, since Henochilus is the sister-group of B. ferox and B. insignis. The most basal species analyzed were the trans-Andean species B. henni, B. petrosus, and B. chagrensis.
Keywords: phylogeny; molecular systematics; mitochondrial DNA; fish evolution; systematic